2021
DOI: 10.3389/fpls.2021.727882
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling and Transcriptome Analysis Explains Difference in Accumulation of Bioactive Constituents in Licorice (Glycyrrhiza uralensis) Under Salt Stress

Abstract: Salinity stress significantly affects the contents of bioactive constituents in licorice Glycyrrhiza uralensis. To elucidate the molecular mechanism underlying the difference in the accumulation of these constituents under sodium chloride (NaCl, salt) stress, licorice seedlings were treated with NaCl and then subjected to an integrated transcriptomic and metabolite profiling analysis. The transcriptomic analysis results identified 3,664 differentially expressed genes (DEGs) including transcription factor famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The genes associated with flavonoid biosynthesis are mainly classified into structural and regulatory genes [41]for instance, CHS, FLS, F3H, F3 H, C4H, etc. C4H plays an important role in flavonoid biosynthesis [42][43][44]. Correlation analysis showed that C4H at all three ripening stages positively regulated flavonoids including luteolin, hesperetin, homoeriodictyol, phloretin, butin, aromadendrin, naringenin chalcone, and pinobanksin.…”
Section: Discussionmentioning
confidence: 99%
“…The genes associated with flavonoid biosynthesis are mainly classified into structural and regulatory genes [41]for instance, CHS, FLS, F3H, F3 H, C4H, etc. C4H plays an important role in flavonoid biosynthesis [42][43][44]. Correlation analysis showed that C4H at all three ripening stages positively regulated flavonoids including luteolin, hesperetin, homoeriodictyol, phloretin, butin, aromadendrin, naringenin chalcone, and pinobanksin.…”
Section: Discussionmentioning
confidence: 99%
“…This plant is actively being studied due to its economic importance; the analysis of its transcriptome [8,9], and the assembly and annotation of its draft genome [10], and complete chloroplast [11] and mitochondrial [12] genomes, have been carried out to date. Recently, the effects of different stressors on transcriptome activity in G. uralensis plants have also been analyzed [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome studies are increasingly expanding from model plants to non-model plants, and plant gene sequence analysis has greatly expanded plant databases. It has been shown that differences in the expression of genes based on metabolic pathways can be used to investigate the regulation of secondary metabolite synthesis and accumulation at the molecular level during plant development [45]. At present, the whole chloroplast genome of TH has been sequenced, but because TH is not a model plant the study of transcriptome data of TH is limited.…”
Section: Discussionmentioning
confidence: 99%